Self-Care Practices in Families with Stunted Toddlers : A Literature Review - Nurhafizah Nasution; Tukimin Bin Sansuwito (International Journal of Health and Medicine, 2024)
The prevalence of stunting in toddlers remains a significant global health concern, particularly in developing countries. This literature review aimed to examine the effectiveness of self-care practices in families with stunted toddlers and identify successful intervention strategies. A systematic search was conducted across three major databases: PubMed, Scopus, and Google Scholar, yielding 48 articles, of which 15 met the inclusion criteria. The review revealed that successful interventions typically incorporated comprehensive educational programs, strong community health worker engagement, robust family support systems, and integration with existing healthcare infrastructure. Key findings highlighted the importance of cultural adaptation, family empowerment, and community involvement in stunting prevention programs. Implementation barriers included resource limitations, cultural beliefs, knowledge gaps, and healthcare access challenges. The studies, particularly from Indonesian contexts, demonstrated that culturally adapted, family-centered interventions yielded significant improvements in child growth outcomes and family self-care practices. However, limitations in study duration and scope suggest the need for more long-term research to evaluate intervention sustainability. This review provides valuable insights for healthcare providers and policymakers in developing effective stunting prevention strategies.